Student Character Rehabilitation Model Through the Tazkiyah Al-Nafs Program - Muslikhin; Sam'un; Mohammad Aqil Baihaqi; Nina Napisah; Bambang Samsul Arifin (Jurnal al-Thullab, 2025)
This study aims to analyze the influence of the Tazkiyah al-Nafs program on the character development of students at Madrasah Aliyah Ihyaul Ulum Gresik. This research employed a quantitative approach using a survey method, with data collected primarily through questionnaires. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS software. The results indicate that Self-Purification has a highly significant impact on students’ religiosity and social empathy. Self-Control contributes strongly to religiosity and social empathy, while Spiritual Self-Awareness has a significant effect on personal responsibility. Furthermore, Consistency in Righteous Deeds plays an important role in shaping self-discipline. Conversely, several hypotheses were not supported, such as the influence of Closeness to God on self-discipline and personal responsibility, as well as the influence of Spiritual Self-Awareness on social empathy. These findings suggest that spiritual values have not been fully internalized into actual behavior and require more experience-based and action-oriented programs. This model offers an integrative approach to character rehabilitation, systematically combining spiritual intervention (Takhliyah), the cultivation of noble character (Tahliyah), and self-actualization (Tajalliyah) in the school environment.